Community Behavior Factors in Environmental Health Care: An Exploratory Study - Ni Nyoman, Nuartini; NLP, Dina Susanti; I Made, Sudarsana; Sutini, Ni Kadek (Babali Nursing Research, 2024)
Introduction: Maintaining a universal balance is one goal of environmental cleanliness. Environmental cleanliness is difficult to handle in Bali, especially in Tabanan. The government involves the village to solve this problem. The goals are to explore the leading and inhibiting factors influencing people's behavior to maintain environmental health and realize the balance of tri hita karana. Methods: This study employed qualitative and explorative. Ten participants were interviewed using in-depth interviews. Data was validated by source triangulation (community, community leaders, health workers) and analyzed thematically. Results: The themes were determinant factors that lead to community behavior, inhibiting factors of community behavior, and community perceptions in environmental health maintenance. The categories were the leading factors that influence community behavior, community awareness and motivation for the importance of environmental health, the role, support, and outreach of the village and community leaders, and the availability of facilities in the form of waste disposal sites (TPS). The inhibiting factors were that many people had vacant land to dispose of garbage, access to information media needed to be improved, and facilities and infrastructure required to be added. The public's perception of environmental cleanliness associated with the tri hita karana concept was good and supported this effort.Conclusion: Several factors influence people's environmental behavior toward tri hita karana. These factors include leading, inhibiting, and influencing people's perceptions of environmental cleanliness when associated with tri hita karana. When connected with efforts to tri hita karana, keeping the environment clean is expected to help create harmonious human relations with nature, which can directly or indirectly impact human-to-human relations and human relations with God.